Severe pain management in the emergency department: patient pathway as a new factor associated with IV morphine prescription - Lvovschi, Virginie E.; Carrouel, Florence; Hermann, Karl; Lapostolle, Frédéric; Joly, Luc-Marie; Tavolacci, Marie-Pierre (Frontiers in Public Health, 2024)
Worldwide, between 25% and 29% of the population suffers from pain. Pain is the most frequent complaint in the emergency department (ED) and is involved in 70% of all ED visits. The effective management of acute pain providing appropriate analgesia. Intravenous (IV) morphine protocols based on patient-reported scores, immediately at triage, are currently recommended. They are not systematically prescribed. Physicians probably individualize opioid pain management for each patient and according to care pathway to determine the best benefit-risk balance. Few data are available regarding bedside organizational factors involved. This study aimed to determine the organizational factors associated with no IV-morphine prescription in a standardized context of opioid management in a tertiary-care ED.A 3-month prospective study with a case-control design was conducted in a French university hospital ED. This study focused on factors associated with protocol avoidance despite a Visual Analog Scale (VAS)≥60 or Numeric Rating Scale (NRS)≥6 at triage. Pain components, physicians' characteristics, patients' epidemiological characteristics, and care pathways were considered. Qualitative variables were compared by Fisher's exact test. Continuous variables were compared by Student's t-test. Factors associated with morphine avoidance were identified by logistic regression.Results: 204 patients were included. 46 cases (IV morphine) and 158 controls (IV morphine avoidance) were compared (3:1 ratio). Pain components and patient characteristics were not associated with IV morphine prescription, as patients' epidemiological characteristics. Regarding NRS intervals, results suggest a practice disconnected from first patients' self-report. IV morphine avoidance was significantly associated with care pathways. A significant difference between IV morphine group and no IV-morphine group was observed for "self-referral" (Adjusted Odds Ratio (aOR) 5.11, 95%CI 2.32-12.18, p<0.0001) and patients' trajectories (Fisher's exact test; p < 0.0001), suggesting IV morphine avoidance in ambulatory pathways. In addition, "Junior physician grade" was also associated with IV morphine avoidance (aOR 2.35, 95%CI 1.09-5.25, p=0.03) but not physician gender. This bedside case-control study highlights that the IV morphine avoidance in the ED could be associated with ambulatory pathways and confirms the decreased relevance of "NRS-only" IV morphine protocols for all patients, including non-trauma patterns. Modern pain education should propose new tools for pain evaluation, integrating ED pathway heterogeneity.